Alcohol and drug use during unprotected anal intercourse among gay and bisexual men in Scotland: what are the implications for HIV prevention?. (17th December 2013) - Li, Jessica; McDaid, Lisa M
Abstract : Objectives: To examine alcohol and drug use during unprotected anal intercourse (UAI), and whether use is associated with HIV-related risk behaviours among gay and bisexual men in Scotland. Methods: Cross-sectional survey of 17 gay commercial venues in Glasgow and Edinburgh in May 2011 (n=1515, 65.2% response rate); 639 men reporting UAI are included. Results: 14.4% were always and 63.4% were sometimes drunk during UAI in the previous 12 months; 36.3% always/sometimes used poppers; 22.2% always/sometimes used stimulant or other recreational/illicit drugs; and 14.1% always/sometimes used Viagra. All were significantly correlated and, in multivariate analysis, the adjusted odds of having UAI with 2+ partners in the previous 12 months were significantly higher for men who reported stimulant or recreational/illicit drug use during UAI (AOR=2.75, 95% CI 1.74 to 4.34) and the adjusted odds of UAI with casual partners were higher for men who reported poppers use (AOR=1.50, 95% CI 1.03 to 2.17). Men who reported always being drunk during UAI were more likely to report UAI with 2+ partners (AOR=1.68, 95% CI 1.01 to 2.81), casual partners (AOR=2.18, 95% CI 1.27 to 3.73), and partners of unknown/discordant HIV status (AOR=2.14, 95% CI 1.29 to 3.53), than men who were not. Conclusions: Our study suggests alcohol and drug use may be relatively common during UAI among gay and bisexual men in Scotland. Brief alcohol or drug interventions, particularly in clinical settings, are justified, but should be properly evaluated and take into account the potential influence of broader, situational and social factors on sexual risk.